THE USE OF SEMI-THIN SECTION METHOD IN THE STUDY OF STRESS-INDUCED STRUCTURAL CHANGES IN LUNGS - Koptev, M.M.; Vynnyk, N.І.; Kokovska, O.V.; Filenko, B.M.; Bilash, S.M. (World of Medicine and Biology, 2018)
The perfect knowledge of the microscopic structure of the appropriate organ is crucial in the solution of many urgent problems of clinical medicine. Better preservation of tissue structures is achieved when the tissues are embedded into epoxy resins followed up with the semi-thin section making. In contrast to the thick sections that are used for light microscopy, due to the greater awareness and relative cost effectiveness without the need of complicated expensive equipment, the method of semi-thin sections today is currently used in morphological studies. The paper was aimed at the study of the prospects of using the semi-thin section method to evaluate the immobilization stress-induced structural changes in the lungs. The resulting study showed the appropriateness of the use of semi-thin sections to study structural changes in lungs, induced by the experimental stress. The study of the semi-thin sections is the beneficial technique of the morphological analysis that permits to evaluate the structure of the studied material at the tissue and cellular level.
Keywords: semi-thin sections; lungs; stress